Anaerobically incubated nitrogen improved nitrogen diagnosis in corn - Orcellet, Juan Manuel (2017)
Current N diagnostic methods for corn (Zea mays L.) are often based on the nitrate nitrogen (NO3 ––N) concentration before planting (pre-plant nitrate test, PPNT) and nitrate nitrogen (NO3––N) concentration at V6 stage (PSNT). These tests provide scant information on soil N mineralization during the growing season, which can supply a considerable proportion of corn N requirements. The objective of our study was to evaluate if in-season N recommendations could be improved by inclusion of a N mineralization potential estimator. We conducted field experiments (n = 35) in three different areas and in two planting dates. At each site we evaluated PPNT, PSNT, and NH4–N released during anaerobic incubation (Nan), which were then related to corn yield in unfertilized plots (0N) and corn response to nitrogen fertilization (Nresp%) using multiple regression analysis. The sole incorporation of Nan to PPNT and PSNT models improved their capacity to predict corn yield in 0N plots and Nresp% only in areas with similar edaphic-climatic characteristics. Independently of the geographical region, when PPNT and PSNT were combined with Nan, texture, and temperature, their capacity to predict yield in 0N plots was increased (PPNT: from R2 0.02–0.47; PSNT: from R2 0.09–0.53), as it was their capacity to estimate Nresp% (PPNT: from R2 0.06–0.23; PSNT: from R2 0.19–0.42). The inclusion of Nan can improve traditional N diagnostic models when it is combined with edaphic/climatic properties that account for the mineralization rate of this N pool.